KETAHANAN BEBERAPA GENOTIP PADI LOKAL BANGGAI TERHADAP SERANGAN WERENG COKLAT (Nilaparvata lugensSTALL) (HEMIPTERA: DELPHACIDAE) - Purnama Sari,Mohammad Yunus, Hasriyanty, Intan (AGROTEKBIS, 2015)
The objective of this research was to study the resistance of several genotype of local Banggai rice crop to brown planthopper (Nilaparvata lugens Stall). This research was carried out at the screen house of pest and diseases plant Laboratory Agriculture Faculty Tadulako University, Palu,on September 2014 to January 2015. Four genotypes of local Banggai rice plant (Njengi, Habo, Ranta and Sampara), were tested  that performed, there are three genotypes (Njengi, Ranta, and Sampara) moderately resistantto brown planthopper,and one genotype (Habo),was  categories of moderately susceptibleto brown planthopper.The highest damage level was shown by genotype Habo ( 65 % ), and the lowest were Njengi and Sampara genotype ( 59 % ).